Kearifan Lokal Handep Masyarakat Dayak: Perspektif Cendekiawan Muslim Dayak di IAIN Palangkaraya Raya - Husni, Muhammad (Rihlah: Jurnal Sejarah dan Kebudayaan, 2020)
This research is based on the local wisdom culture of the Dayak people which is used as a philosophy of life which is derived from the values of handep (gotong royong) in the form of equality, brotherhood, kinship and tolerance. On this basis, the main problem of this research is howcultural activities handep in the Dayak community are in the perspective of Dayak Muslim scholars as academics at IAIN Palangka Raya, so this research aims to describeactivities handep with the values they have that contribute to the realization of brotherhood in a society multicultural. This study used a qualitative approach to 14 academics at IAIN Palangka Raya. The technique of collecting data is conducting in-depth interviews with sources with the help of recording tools and stationery. Data analysis was carried out during the research process carried out until drawing conclusions then analyzing the data, namely data collection, data reduction, data presentation and presentation of conclusions. The results showed that the values incultural activities handepstrong gave birth toharmony, harmony, unity and brotherhood through mutual cooperation instruments in terms of clearing land, farming, building houses, traditional marriage ceremonies, traditional ritual ceremonies and togetherness at death ceremonies. by visiting each other and making contributions. Penelitian ini didasarkan pada budaya kearifan lokal masyarakat suku Dayak yang dijadikan falsafah hidup yang diturunkan dari nilai-nilai handep (gotong-royong) berupa nilai kesetaraan, persaudaraan, kekerabatan dan toleransi. Atas dasar tersebut yang menjadi masalah pokok penelitian ini adalah bagaimana aktivitas budaya handep di masyarakat Dayak dalam perspektif cendekiawan Muslim Dayak selaku akademisi di IAIN Palangka Raya, sehingga penelitian ini bertujuan untuk mendeskripsikan aktivitas handep dengan nilai-nilai yang dimiliki yang berkontribusi bagi terwujudnya persaudaraan dimasyarakat yang multikultural. Penelitian ini menggunakan pendekatan kualitatif terhadap 14 orang akademisi di IAIN Palangka Raya. Teknik pengumpulan data yaitu melakukan wawancara mendalam kepada narasumber dengan bantuan alat rekam dan alat tulis. Analisis data dilakukan selama proses penelitian dilaksanakan hingga penarikan kesimpulan kemudian menganalisis data, yaitu koleksi data, reduksi data, penyajian data dan pemaparan kesimpulan. Hasil penelitian menunjukkan bahwa nilai-nilai dalam aktivitas budaya handep melahirkan kerukunan, keharmonisan, persatuan, dan persaudaraan yang kuat melalui instrumen gotong-royong dalam hal membuka lahan, bercocok tanam, membangun rumah, upacara adat perkawinan, upacara ritual adat dan kebersamaan pada upacara kematian dengan saling mengunjungi serta memberi kontribusi.